Epidemiology and pathophysiology of sepsis: an review (Research, Society and Development, 2020)
Sepsis is an organ dysfunction secondary to an infection, in which the patient develops an unregulated response to this aggression. It is considered one of the leading causes of mortality in critically ill patients, being related to high prevalence and mortality rates worldwide. Based on this explanation, this paper presents a literature review, highlighting the epidemiology and pathophysiology of sepsis. This article is an narrative review, covering scientific articles, monographs, theses and dissertations published in the databases: CAPES, SciELO and Google Scholar. Studies show that sepsis is a serious public health problem in the Intensive Care Unit (ICU), which despite a huge research effort in recent decades remains a considerable and growing challenge to health care. Finally, it is concluded that the main objective of the study can be achieved, and being a pathology with critical, acute and high prevalence, it is necessary to know about its causes, epidemiology and pathophysiological processes.